2021
DOI: 10.3389/fendo.2021.626427
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Insulin and Pituitary Hormone Syndromes

Abstract: Pituitary hormone axes modulate glucose metabolism and exert direct or indirect effects on insulin secretion and function. Cortisol and growth hormone are potent insulin-antagonistic hormones. Therefore impaired glucose tolerance, elevated fasting glucose concentrations and diabetes mellitus are frequent in Cushing’s disease and acromegaly. Also prolactinomas, growth hormone (GH) deficiency, hypogonadism and hypothyroidism might be associated with impaired glucose homeostasis but usually to a lesser extent. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Hypopituitarism (including central hypogonadism), reported in 10–80% of acromegalic cases, and hyperprolactinemia (affecting more than one third of the patients) are associated with a higher rate of subfertility/infertility in acromegalic patients when compared to a non-acromegalic population of the same age, in both females and males [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Pituitary insufficiency and increased prolactin status are related to larger tumors; 90–95% of pituitary GH secreting tumors are macroadenomas; the additional negative role concerning fertility status is caused by secondary DM [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. For instance, one study from 2022 on 529 acromegalic individuals identified a rate of hyperprolactinemia of 39.1% and a prevalence of hypopituitarism of 34.8%, with the gonadal axis being the most affected pituitary axis; there was a hypogonadism frequency of 29.7% [ 45 ].…”
Section: Sub/infertility Issues In Acromegalymentioning
confidence: 99%
“…Hypopituitarism (including central hypogonadism), reported in 10–80% of acromegalic cases, and hyperprolactinemia (affecting more than one third of the patients) are associated with a higher rate of subfertility/infertility in acromegalic patients when compared to a non-acromegalic population of the same age, in both females and males [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Pituitary insufficiency and increased prolactin status are related to larger tumors; 90–95% of pituitary GH secreting tumors are macroadenomas; the additional negative role concerning fertility status is caused by secondary DM [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. For instance, one study from 2022 on 529 acromegalic individuals identified a rate of hyperprolactinemia of 39.1% and a prevalence of hypopituitarism of 34.8%, with the gonadal axis being the most affected pituitary axis; there was a hypogonadism frequency of 29.7% [ 45 ].…”
Section: Sub/infertility Issues In Acromegalymentioning
confidence: 99%
“…Even subtle variations in sleep characteristics are likely to influence health via metabolic, endocrine and cardiovascular processes to adversely influence health. For instance, sleep impairments can lead to several hormonal changes that result in lower response of β cells to glucose and reduced insulin sensitivity (driven by lower glucagon‐like peptide‐1 levels) 40 . Conversely, modification of these behaviours through sleep interventions (e.g., sleep extension, sleep education or cognitive behavioural therapy for insomnia) has the potential to influence a number of health outcomes, including insulin sensitivity and energy intake 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial Rho proteins MIRO regulate mitochondrial trafficking and local energy turnover in neurons, affecting the neurodegeneration process [72]. These Rho proteins regulate hormone secretion in PAs [45] and maintain glucose homeostasis [73], which is altered in both acromegaly and Cushing's individuals [74]. MAPK signalling cascade regulates biological processes such as stress, proliferation, apoptosis and immune defence [44].…”
Section: Discussionmentioning
confidence: 99%